PERSEPSI MAHASISWA TERHADAP PERATURAN PEMADANAN NIK MENJADI NPWP DAN DAMPAKNYA TERHADAP PENINGKATAN KEPATUHAN PAJAK - Chelsya Chelsya; Verawati Verawati (Universitas Islam Negeri Alauddin Makassar, 2023)
The role of taxes in the economy in Indonesia is enormous because taxes play a role in maintaining the balance of the country's economy and helping to create social welfare. A tax collected from tax objects and subjects is used to build public facilities for society. However, some still have income above PTKP but still need to pay and report taxes. Therefore, the government is trying to improve tax compliance by establishing a new regulation that matches NIK as NPWP. By checking NIK to NPWP, a Single Identification Number (SIN) is created so that people only need to bring 1 KTP card for administrative purposes. This study aims to determine students' perceptions and understanding of the rules for matching NIK to NPWP and their impact on increasing tax compliance. This research is descriptive research with a quantitative approach using the survey method. The results showed that students were already aware of the regulations for matching NIK to NPWP and their procedures through online media and socialization provided at the University. While the cause of the failure of NIK validation to NPWP is due to not fulfilling the requirements as a taxpayer, and the confirmation process via email has yet to be activated. Kata Kunci : Tax; NIK; NPWP; Tax Compliance